Genetic divergence in corn with forage potential in the Municipality of Santa Maria of Barreiras-PA - Santos, Weder Ferreira dos; Marinho, Maria Angelica Oliveira; Santos, Layanni Ferreira Sodré; Peluzio, Joênes Mucci; Carneiro da Silveira Tschoeke, Marcela Cristina Agustini; Siqueira, Guilherme Benko de; Cerqueira, Fernando Barnabé; Ferreira, Talita Pereira de Souza; Fidelis, Cícero Antonio Sobreira; Silva, Laura Carneiro; Oliveira, Magno de (International Journal of Advanced Engineering Research and Science, 2021)
The objective of this work was to estimate the genetic divergences in corn with forage potential in the southern region of Pará. Two competition trials of corn cultivars were installed, one under high nitrogen (150 kg ha-1from N) and another under low N (0 kg ha-1from N) applied in Cobertura, a crop 2020/21 in the State of Pará (8°18’32’’S, 50°36’58’’O,150 meters of altitude). The experimental design used in each assay was randomized blocks with three replicates and 11 maize cultivars, three varieties of open pollination, one single hybrid, seven double hybrids, and one triple hybrid. The following characteristics were analyzed: plant height (AP) in cm, the height of spike (AE), stem diameter (DC), spike diameter (DE), stem and leaf pasta (MCF), spike mass (ME),and full plant mass (MTP). For the analysis of genetic divergence, dissimilarities measures were used that were determined according to the multivariate analysis model, allowing the achievement of dissimilarities, residual covariances, and means of populations. Genetic divergence was evaluated by multivariate procedures with the generalized Mahalanobis distance, the Tocher optimization clustering method, and Singh's criterion to quantify the relative contribution of the seven characteristics. By estimating Mahalanobis distances, maize genotypes AG8088PRO2 X P33-16 showed a greater distance. The Tocher method was efficient in separating the groups. The characteristics of full plant mass and mass of stem and leaf were the ones that most contributed to genetic divergence.